Hemoadsorption Treatment with CytoSorb® in Probable Hemophagocytic Lymphohistiocytosis: A Role as Adjunctive Therapy?. (21st August 2021) - Ceruti, Samuele; Glotta, Andrea; Adamson, Harriet; Mauri, Romano; Molnar, Zsolt
Abstract : Acute hemophagocytic lymphohistiocytosis (HLH) is a life-threatening disease, with an annual incidence of 1 : 800, 000 people. The disease is characterized by a cytokine storm, with concomitant macrophage and natural killer (NK) cell activation; death can occur from multiple organ failure or complications such as bleeding diathesis. Therefore, HLH treatment remains a challenging one. We hereby present a case of a 76-year-old man with severe HLH in whom hemoadsorption was successfully applied. Due to the failure of the immunomodulatory therapy, continuous venovenous hemodiafiltration therapy with the CytoSorb® adsorber was successfully applied for 48 hours. Upon therapy discontinuation, the biological and clinical condition reverted, unfortunately evolving towards the patient's death.